Exploring how grade 7 learners solve additive word problems - Mochosa, Karabo Ngako (University of the Witwatersrand, Johannesburg, 2024)
This report focuses on the role that the dynamic model of the bar model and number line can play in redirecting learners from a non-formal understanding associated with the real or imagined reality to an understanding of formal systems (Van den Heuvel Panhuizen, 2003). My investigation is located within two grade 7 classes in a school at Johannesburg, one class was the control group and the other was the intervention group, the control group was not exposed to any tools that can help improve and support the learner’s informal solution strategies, whereas the intervention had an exposure. In addition to researching the models that learners use before the intervention courses, I was the teacher of the six intervention lessons on additive relation problems. This report presents evidence that learners struggle with working with abstract calculations. However, with proper intervention, learners can make important changes toward more abstract calculations. In addition, the most important finding is that most of the problems were approached using the column model in the pre- and post-test of the control group, and the pre-test of the intervention group. This confirms that this model has been encouraged by most schools for learners to use from the beginning of the intermediate phase. Also, the results show that most questions in both the control group's pre-test and posttest as well as the intervention group's pre-test had a significant percentage of wrong answers due to the usage of the column model. On the other hand, the post-test of the intervention group had very fewer problems that were tackled using the column model. The use of the bar model and number line in the post-test of the intervention group was the one mostly used and it was associated with a proportion of correct answers, this suggests that improvements can be achieved in a short period of time.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; additive word problems; Grade 7; SDG-4: Quality education